1989
DOI: 10.1007/bf00414437
|View full text |Cite
|
Sign up to set email alerts
|

Photokilling of bacteria by the natural dye curcumin

Abstract: Curcumin is a yellow-orange compound derived from the root of Curcuma longa (Zingiberaceae family), that has been used as a medicine, spice and coloring agent. Curcumin has proved nontoxic in a number of cell culture and whole animal studies. Curcumin has, however, been reported to have bactericidal effects at very high concentrations. When illuminated, curcumin exerted potent phototoxic effects in micromolar amounts. Gram-negative bacteria displayed greater resistance to curcumin phototoxicity relative to Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
0
14

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 5 publications
6
110
0
14
Order By: Relevance
“…Thus, although promising results were described with the use of CUR without light excitation, higher concentrations of the compound were needed to induce the antifungal effect. Likewise, the studies of Dahl et al [34] and Tønnesen et al [35] reported that the antibacterial activity of some CUR concentrations was greatly enhanced by light. Another finding in the present study was that PDT effectiveness was not always fluence-dependent.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, although promising results were described with the use of CUR without light excitation, higher concentrations of the compound were needed to induce the antifungal effect. Likewise, the studies of Dahl et al [34] and Tønnesen et al [35] reported that the antibacterial activity of some CUR concentrations was greatly enhanced by light. Another finding in the present study was that PDT effectiveness was not always fluence-dependent.…”
Section: Discussionmentioning
confidence: 90%
“…This hypothesis can be sustained by the work published by Dahl [15] that investigated the oxidation capability of singlet oxygen on Gram-positive and Gram-negative bacteria. The authors concluded that this extremely reactive free radical presents a very short lifetime (in order of 0,04 µs) and low diffusion capacity.…”
Section: Discussionmentioning
confidence: 90%
“…The bactericidal effect of light-irradiated curcumin occurs at relatively short drug-light intervals (0-60 min), whereby longer drug-light intervals (90 min) did not yield an additional cytotoxic effect [95]. These data suggest that curcumin either distributes rapidly throughout the cell or confers its phototoxic effect at superficial loci, from which the generated radical intermediates may induce local damage or diffuse to intracellular targets.…”
Section: Curcuminmentioning
confidence: 86%
“…The photokilling propensity of curcumin was considerably more profound in the Gram-positive S. aureus than the Gramnegative E. coli and Salmonella typhimurium (~300 times more effective when corrected for light dose and concentration) [95], indicating an associative predilection for Gram-positive species. The bactericidal effect of light-irradiated curcumin occurs at relatively short drug-light intervals (0-60 min), whereby longer drug-light intervals (90 min) did not yield an additional cytotoxic effect [95].…”
Section: Curcuminmentioning
confidence: 96%